Collaborative and Cooperative Learning in Malaysian Mathematics Education - Hossain, Md. Anowar; Tarmizi, Rohani Ahmad; Mohd Ayub, Ahmad Fauzi (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2012)
Collaborative and cooperative learning studies are well recognized in Malaysian mathematics education research. Cooperative learning is used to serve various ability students taking into consideration of their level of understanding, learning styles, sociological backgrounds that develop students’ academic achievement and skills, and breeze the social harmony among students of different ethnic backgrounds. Besides academic achievement, process skills and values are required to extend the social harmony among students in today’s multiethnic schools. Therefore, teachers are expected to find the pedagogy that enables students to learn academic knowledge and professional skills to face the challenges in their everyday lives. The Malaysian scholars, based on the findings of their cooperative learning studies, emphasized the use of cooperative learning as an effective pedagogy with the aim to improve students’ mathematics achievement and communication skills. This paper describes the role of collaborative and cooperative learning to the development of students’ mathematics achievement along with their communication skills and with significant integration of values in Malaysian mathematics education.